“Conservative” Verse by V. V. Nabokov: Specifics of Constructing Verse Vertical - O. S. Laletina; E. V. Khvorostjanova (Научный диалог, 2022)
The article deals with the problem of experimenting by V. V. Nabokov the poet. The novelty and relevance of the study are due to the fact that the poet’s work, taken in the most complete volume to date (578 works, 18470 lines), is not the material of a traditional level-by-level poetic description, but a correlation analysis that takes into account the parameters of the formation of the verse vertical (poetic meter, strophic structure, clause, rhyme). The proposed method made it possible to reconsider the established idea of the conservatism of Nabokov the poet and to identify specific strategies for constructing a poetic vertical. It is proved that Nabokov cannot be called a poet who revived the metrical preferences of Pushkin’s time: the proportions of two-syllables, the variety of non-classical meters testify to his closeness to the authors of the first half of the 20th century. It has been established that the specificity of Nabokov’s experiments is determined by the use of the principles of organization of the verse vertical, which consists in the violation of rhythmic inertia due to various interruptions in rhythm — a change in poetic meter, the order of alternation of clauses, rhymes. The identification of these principles made it possible to formulate a hypothesis about the commonality of the construction of Nabokov’s poetic narrative with the prose narrative, in which the violation of the established convention, according to the general opinion of literary critics, is one of the main features.